Analisis Alokasi Air Dengan Metode FPR-LPR dan Evapotranspirasi Pada Tanaman Padi (Oryza sativa L.) di UPT SDA Balung Daerah Irigasi Bedadung - Suci Ristiyana; Romadhona Destria Putri; Tri Ratnasari; Ika Purnamasari; Tri Wahyu Saputra; Sri Irawan Laras Prasojo (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2025)
Rice is one of the agricultural commodities that serves as the foundation of food security. Rice production fluctuates from year to year. Rice production in Jember Regency is mostly produced from irrigated rice fields. Bedadung irrigation area is one of the irrigation areas that has a large service area. UPT Balung is one of the UPTs that often experience water shortages. efforts that can be made to meet agricultural water needs are by optimizing water allocation management in agricultural land. Methods that can be used for water allocation management are the FPR-LPR and evapotranspiration methods. The purpose of this study is to determine the allocation of water, cropping patterns and the best method between the FPR-LPR and evapotranspiration methods on rice plants in UPT Balung Bedadung irrigation area. The research requires data in the form of secondary data which includes climate element data, soil data, crop data and 2022-2023 RTTG data. Water allocation using the FPR-LPR method shows that in growing season 1 requires water of 81,612 l/sec and in growing season 2 of 22,152 l/sec. Water allocation using the evapotranspiration method shows that in growing season 1 requires water amounting to 13,152 l/sec and in growing season 2 amounting to 15,196 l/sec. The best method between the two methods is the evapotranspiration method because the evapotranspiration method is based on climate data, soil data and crop data.